2018
DOI: 10.1002/mabi.201800196
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Anti‐Biofilm Activities of Surface Engineered Polycationic Albumin Nanoparticles with Reduced Hemolytic Activity

Abstract: Protein-based polymeric polyelectrolytes are emerging as alternative synthetic nanoparticles owing to their biodegradability and biocompatibility. However, potential in vivo toxicity remains a significant challenge. Herein an array of protein polyelectrolytes generated from cationic human serum albumin (cHSA) and polyethylene glycol (PEG) are synthesized via synthetic customization as antimicrobials for the treatment of systemic infections. By varying PEG molecular weight and chain length, in vitro hemolytic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
(56 reference statements)
1
10
0
1
Order By: Relevance
“…The complexation of proteins and polysaccharides via non covalent interactions, such as hydrophobic and electrostatic ones, has been previously evaluated for the formulation of nanoparticles [ 33 , 34 ]. Even if recently antibacterial properties of albumin have been also hypothesized [ 35 , 36 , 37 ], albumin nanoparticles for antibiotic delivery have not been deeply investigated and to date no such formulations loaded with Colistin have been developed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complexation of proteins and polysaccharides via non covalent interactions, such as hydrophobic and electrostatic ones, has been previously evaluated for the formulation of nanoparticles [ 33 , 34 ]. Even if recently antibacterial properties of albumin have been also hypothesized [ 35 , 36 , 37 ], albumin nanoparticles for antibiotic delivery have not been deeply investigated and to date no such formulations loaded with Colistin have been developed.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to results obtained by Pastor M et al [ 46 ] using sodium Colistin methate-loaded lipid nanocarries and by Sans-Serramitjiana E et al [ 23 ] using nanoencapsulated Colistin sulfate that demonstrated an identical activity of free and loaded Colistin against biofilm prevention of P. aeruginosa , we noticed a great effect of our albumin nanoparticles to prevent biofilm formation of A. baumannii . Recently, an effect of PEG-cHSA (cationic human serum albumin) was observed only using MIC and supra-MIC concentrations to prevent P. aeruginosa biofilms [ 35 ]. The biofilm-modulating action of MIC and sub-MICs depends on many factors: type of antimicrobial, mode of action, bacterial strain and susceptibility or resistance of the strain.…”
Section: Discussionmentioning
confidence: 99%
“…Albumin nanoparticles have recently emerged as alternative carrier for various types of diseases. Sybil et al established an array of protein polyelectrolytes generated from cationic human serum albumin (c-HSA) and polyethylene glycol (PEG), which were synthesized via synthetic customization as antimicrobials for the treatment of systemic infections. Woods et al demonstrated that albumin particles were well tolerated in the mouse lung and exhibits a long residence time after deposition (>48 h) .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, metallic nanoparticles are limited by toxicity concerns (e.g., naked iron oxide nanoparticles) and aggregation issues (e.g., silver nanoparticles) [28,29]. Similarly, the chemical composition of polymeric nanoparticles, physicochemical properties (e.g., surface potential) and/or their subsequent degradation products have also been associated with cell toxicity, stress and inflammatory responses [30][31][32]. Recent strategies to uncover advanced delivery systems with improved physicochemical properties and antibacterial effects include the development of nucleic acid nanocarriers and their conjugates.…”
Section: Introductionmentioning
confidence: 99%